A Comparison of Selection Methods for the Improvement of Sorghum Population KU.8 - Watcharin Soonsuwon; Krisda Samphantharak; Wasana Wongyai (Agriculture and Natural Resources, 1994)
A comparison of three population improvement methods was conducted by using S1 seed, sibbed seed and S2 seed of selected S1 lines for a recombination of new cycle. Three hundred S1 lines were selected from KU. Pop.8C0 snd tested in the progeny trial. The best 3-5 female plants and 3-5 male plants from each line were sibbed and selfed to form sibbed seed and S2 seed. Thirty-three S1 lines and their respective derived sibbed seed and S2 seed were chosen to form three new populations namely, KU. Pop. 8(S1)C1, KU.Pop. 8(Sib) and KU.Pop. 8(S2) C1. Resulted data proved that S1 seed and its derived sibbed seed and S2 seed were very effective for increasing grain yield of new cycle populations. The highest yielding population was KU.Pop.8(S2)C1 which yield 5.82 ton/ha followed by KU.Pop.8(Sib)C1, 5.72 ton/ha and the lowest yielding population was KU.Pop.8(S1) which yielded 5.59 ton/ha. However, the yield of three new populations were not different statistically. KU.Pop.8(S2)C1, KU.Pop.8(Sib) C1 and KU.Pop.8(S1)C1 yield 11, 9 and 7 percent over KU.Pop.8C0 , which was used as the original check population, respectively. The new populations were also improved for serveral other agronomic traits, such as higher 1,000 seed weight, higher shelling percentage, shorter panicle length, less lodging percentage and less leaf diseases.